The role of endoplasmic reticulum stress in the MHC class I antigen presentation pathway of dendritic cells. (April 2022) - Manoury, Bénédicte; Maisonneuve, Lucie; Podsypanina, Katrina
Abstract: Dendritic cells (DCs) have the unique capacity to link innate to adaptive immunity. While most cells that express major histocompatibility (MHC) molecules are able to present antigens to activated T cells, DCs possess the means for presenting antigens to naïve T cells, and, as such, are able to instruct T cells to initiate immune response. There are two cascades of events necessary for DCs to start their instructive function. First, DCs enzymatically process proteins to make T cells recognize an antigen as unique peptide-MHC complexes. Second, DCs provide secretory cytokines and co-stimulatory functions for T cells to respond to this antigen. Thus, the compartments for protein degradation and for protein synthesis are central to DC function. The endoplasmic reticulum (ER), a vast network of membranes and vesicles, connects these compartments and helps modulate DC-specific performance, such as antigen capture and presentation. However, while the health of ER appears relevant for DC function, the intersection between ER stress and antigen presentation remains to be explored.